Review of the Book of Kazakh History and Literature Survey and Analysis of Historical and Literary Links with Iran - Behruz Bekbabayi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The Cossacks, who had were separated from Turkic society in 1465 and had independent identities until Russian domination, also gained extensive geography in Central Asia after independence. But, we know that this vast geography is part of Iran’s cultural geography. Consequently, the historical process of thought and literature in this field is necessary for the investigation of Iranian scientific circles. As a result, in order to achieve this goal, we reviewed the book “Kazakh History and Literature “Survey and Analysis of Historical and Literary Links with Iran” by Islam Zhemeni. In this review, we will mention the positive features of the book, such as providing brief information on the history and culture of the Kazakhs, the various periods of Kazakh literature, especially the literature of the Stalin era, and the way in which the Cossack intellectuals struggled with Stalin’s despotism at the head of them in the process of Kazakh culture and thinking. Particularly, we will refer to the most influential Kazakh indicators, such as Abai Qunanbayoglu, Shahkarim, Mokhtar Avesov, and so on. We will also look at some of the flaws in the book, such as repetition and the emotional content of some of the content and the weakness of the book’s layout and editing. This book is very important in knowing the way and time of the influence of Iranian culture and literature in those areas.